MIGRATION AND INTERLANGUAGE: TRANSLATIVE WRITING IN OSMAN ENGIN’S SATIRICAL TEXTS (Revista de Letras, 2018)
The prose works Deutschling (1985) and Oberkanakengeil (2003) by the German-Turkish novelistOsman Engin satirically invert reigning stereotypes against Turkish immigrants. In both works,Turkish and German act as cultural and linguistic reference systems, which are subverted throughthe strategy of translatory mimicry. This mimicry is an integral element of the narrative structureof Engin’s works and becomes a stylistic singularity, which unbalances the German language andundermines it in its seeming naturalness. Through a close reading of Engin’s works, the contributionaims to offer a deeper understanding of the extent and nature of the unbalancing of cultural andlinguistic points of reference, which implies a deconstruction of collective identities and fi xedideas. In addition to the metalinguistic markings in the hybridized German-Turkish interlanguageof the author, as we will show, the constant alternation between object level and meta level playsan important role in the narrative structure of the texts, resulting in the continuous considerationof the mother tongue’s signifi cance and the issue of intralingual translation.